Mathematical Communication Ability Based on Anyaman Purun Ethnomathematics - Maulina Fakhrunnisa Salsanabila; Marsigit Marsigit; Ali Mahmudi (STAI Hubbulwathan Duri, 2024)
Mathematical communication skills are essential for students to effectively express and understand mathematical ideas. This study investigates these skills within the context of one-variable linear equations and inequalities, incorporating ethnomathematics through the lens of anyaman purun (traditional grass weaving) as a culturally relevant framework. A qualitative descriptive research design was employed. The participants included six grade 7 students selected purposively from a pool of 28 students. Data collection methods comprised tests, interviews, and documentation. Data analysis was conducted following Miles and Huberman’s model, which includes data reduction, data presentation, and conclusion drawing. Triangulation through test results and interviews was used to ensure data validity. Findings revealed that 46.4% of the students displayed high-level mathematical communication skills, 28.6% demonstrated moderate skills, and 25% exhibited low skills. Students with high proficiency effectively conveyed mathematical concepts using written, visual, and mathematical expressions, while those with moderate skills performed adequately in these areas. Students with lower skills faced challenges across all aspects of mathematical communication. The integration of anyaman purun within mathematics instruction highlighted cultural relevance as a tool for enhancing mathematical communication. High and moderate skill levels corresponded with more effective communication and understanding of mathematical concepts, whereas students with lower skill levels struggled with these aspects. The study suggests that incorporating culturally relevant contexts like anyaman purun can improve mathematical communication skills, potentially enhancing learning quality and fostering students' ability to articulate mathematical ideas.